Larvicidal Effect of The Ethanoic Leaf Extract of Chromolaena odorata Against The 4th Instar Larvae of Aedes aegypti - Ugochukwu Anthony Obiakor; Cornelius Orjighjigh Ishar; Gloria Chidubem Ugwuanyi; Benjamin Chidi Umeanor; Patrick Ifeanyi Onuegbu (Journal of Parasite Science, 2026)
Annually, over 700 million people suffer from mosquito borne diseases, some of which include yellow and dengue fever caused by Aedes aegypti. The use of chemical insecticides has led to pest resistance, environmental pollution and destruction of non-target organisms. This complete randomized study was carried out from June to August 2024, to investigate the larvicidal potential of the essential oil extract of Chromolaena odorata leaves against A. aegypti 4th instar larva. Data was analyzed using ANOVA and Probit regression analysis. Different concentrations ranging from 20%, 10%, 5%, and 2.5% were obtained by serial dilution using the dilution factor.  The result shows significant differences P<0.05 in toxicity level of the essential oil extract, which indicates considerable susceptibility of A. aegypti larvae when exposed to oil extract of C. odorata. Highest ethanoic leaf extract concentration of 20% recorded the highest mean mortality (4.33±0.88) while no mortality (0.00±0.00) was recorded at 2.5% concentration. Base on lethal time of exposure, the highest mean mortality was observed at 24 hours (4.67±0.07) followed by 12 hours (3.67±0.58) while the lowest mean mortality was recorded at 3 hours (1.00±0.47). Probit regression analysis showed that lethal concentration, LC50 was 30.21 mg/ml while LC90 was 245.8 mg/ml. The lethal time, LT50 and LT90 were found to be 29.58 hours and 297.8 hours respectively. C. odorata have shown a good larvicidal activity on A. aegypti, thus this suggest that it could serve as an alternative method to synthetic chemical control of the Zika virus, dengue and yellow fever vector.